Flower colour variations in gerbera (Gerbera jamesonii) population using image analysis - SINGH, S; DHYANI, D; YADAV, ASHOK KUMAR; RAJKUMAR, S (The Indian Journal of Agricultural Sciences, 2026)
Image analysis was performed on ligules of 211 progenies and seven parental accessions of gerbera (Gerbera jamesonii Bolus ex. Hooker F), to quantify colour variation. The colour variations were assessed based on mean values of (1) red, green, blue (RGB), (2) hue and saturation (HS) colour channels of ligule colour. Multivariate clustering of genotypes based on RGB and HS colour variables determined the relative position of genotypes in the paired group cluster. The genotypes grouped into different clusters representing distinct colour sub-groups which could be distinguished from each other based on Student’s ‘t’ test. Two major clusters were observed which correspond to the flavonoid and carotenoid pigments which contribute to flower colour variations in gerbera. Analysis of variance among genotypes within each colour cluster revealed significant variations for ligule colour implying high degree of polymorphism for the trait but the extent of variation was lower compared to variations among clusters. Ten pairs of genotypes were identified with similar colour expression, which have potential use in breeding for homogeneous colour expression of gerbera populations.